STUDENTS"™ MOTIVATION IN LEARNING ENGLISH DURING THE ONLINE CLASS - Suhartina, Suhartina; Rezeki, Yanti Sri; Suhartono, Luwandi (Journal of English Education Program, 2022)
This research aims to investigate the impact of the online class on students in learning English and investigate the level of students' motivation in learning English during the online class. This research applied descriptive research on eleventh-grade students of SMK Negeri 2 Pontianak in the academic year 2020/2021. The data collection techniques were measurement and semi-structured interviews, while the tools were questionnaire and interview questions. The findings of this research revealed the negative impacts of the online class, including students"™ difficulties in understanding the teacher"™s explanation and learning materials, problems in creating a conducive atmosphere for learning, and students"™ problems in time management. By contrast, the positive impact of the online class made several students more enthusiastic and more focused on study. Besides, the findings showed that 53% of students were qualified with a moderate degree of motivation. The online class did not significantly change the level of students' motivation in learning English even though the students faced difficulties during the online class.